2018
DOI: 10.1016/j.neuroscience.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Extended Exercise and Memantine Treatment on Adult Neurogenesis in Male and Female Rats

Abstract: Adult neurogenesis has potential to ameliorate a number of disorders that negatively impact the hippocampus, including age-related cognitive decline, depression, and schizophrenia. A number of treatments enhance adult neurogenesis including exercise, NMDA receptor antagonism, antidepressant drugs and environmental enrichment. Despite the chronic nature of many disorders, most animal studies have only examined the efficacy of neurogenic treatments over short timescales (≤1 month). Also, studies of neurogenesis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 82 publications
2
13
1
Order By: Relevance
“…Indeed, combined RUN/MEM treatment increased immature DCX + cell density and reduced activity in both developmentally-born neurons and the broader granule cell population. The neurogenic efficacy of RUN/MEM treatment at 4 months extends our recent finding that 2 months of treatment also increases neurogenesis in male rats [33]. Thus, RUN/MEM is capable of promoting neurogenesis over extended intervals.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Indeed, combined RUN/MEM treatment increased immature DCX + cell density and reduced activity in both developmentally-born neurons and the broader granule cell population. The neurogenic efficacy of RUN/MEM treatment at 4 months extends our recent finding that 2 months of treatment also increases neurogenesis in male rats [33]. Thus, RUN/MEM is capable of promoting neurogenesis over extended intervals.…”
Section: Discussionsupporting
confidence: 82%
“…1C; T29=2.065, P=0.048). Whereas we have previously reported that alternating blocks of RUN/MEM increase neurogenesis (DCX + cells) at 2 months in male rats [33], these results indicate that RUN/MEM treatments can result in sustained increases in neurogenesis that are maintained even after 4 months of treatment.…”
Section: Manipulations Alter Adult Neurogenesis and Dentate Gyrus Volumecontrasting
confidence: 87%
See 3 more Smart Citations